“All-on-a-Tube” POCT of Salmonella in large-volume sample - Lei Wang; Nana Jin; Meixuan Li; Jianhan Lin (Sensing and Bio-Sensing Research)
Point-of-care testing (POCT) of pathogenic bacteria at low concentrations is vital to early warning of bacterial contaminations. A disposable centrifuge tube was reconstructed in this study for sensitive Salmonella detection in large-volume samples, where the entire bacterial detection progress from separation to detection, was performed within the tube. The bottom of this centrifuge tube was assembled with a flexible stirrer containing a pair of circular magnets, which was rapidly rotated using a DC motor to produce the vortex for simultaneous mixing and capture of target bacteria. Besides, immune manganese dioxide nanoflowers were synthesized and used to label target bacteria, followed by mimicking catalyze colorless TMB substrate into blue TMBox product. The product image was captured and analyzed by a smartphone App to quantitatively determine the target bacteria. This POCT centrifuge tube effectively achieved a separation efficiency of approximately 80 % for target bacteria from a 10 mL sample, enabling the detection of target bacteria within the range of 1.3 × 101 to 1.3 × 104 CFU/mL in 1 h, with a low detection limit of 13 CFU/mL. More importantly, this reconstructed centrifuge tube demonstrated its potential as a laboratory consumable for bacterial detection in routine screening owing to the features of low cost, easy operation and high integration.